NEEDS FOR NEW CADASTRAL SURVEYING BUILDING REGION IN THE TOWN OF BAČKA PALANKA - Filipović, Milan; Kuburić, Miroslav; Lero, Mladen (Journal of Applied Engineering Science, 2013)
In this article presented the short overwiev on previews works of cadastral measurements on territory of municipality of Bačka Palanka and direct comparison data on cadastral maps with data on new digital ortophoto plans (aerial photography from 2010.) on the building region in the town Bačka Palanka. Base on that there is suggestion to make new measurements on the building region in the town Bačka Palanka using new technology. According to this the analysis is given in the study („Geoput“ 2010.) which gives available cadastral data and their updating, credibility and level of useable this data in the process of making decisions about economize lend and creating adequate plans for using, classification and arrangement trade and other recourses on this part of building region. The study gives information about cadastral measurements in chronological way from 1864, which carried out in harmony with possibilities of local government and according to plans and programs of work of republic establishment. From other side the study gives suggestion of work on the cadastral measurements in the next period according law regulation and possibility of institutions, which dallies, and which are authoritative in this area.
Keywords: Municipality Bačka Palanka; Civil region; Previews study of reasonable; Cadastral measurements